Improvement of TVET’s Educators Competency in Heutagogy Context - Mohamad, Mimi Mohaffyza; Zakaria, Anies Fazieha; Ahmad, Adnan; Mohd Affendi, Haryanti (Online Journal for TVET Practitioners, 2021)
Heutagogy, otherwise referred to as self-determined learning, is a teaching technique focused on students that emphasize the growth of autonomy, ability, and capacity. The objective of this article is to determine the improvement efforts of TVET educators towards the encountered teaching challenging in the 21st century. A quantitative approach was applied in this research in which. The questionnaire was distributed to TVET educators from 14 selected TVET Institutions. The collected data was organized and analyzed using frequency distribution. This article presents the relationship between the heutagogy element with the level of competency toward improving knowledge, skill, and attitude among TVET educators. According to the study’s findings, most educators have obtained a high level of improvement in knowledge, skills, and attitude competency elements. The Pearson correlation analysis is conducted to determine the relationship of heutagogy element and competency level using p < 0.01 as the significance references. The findings show that there is a strong relationship of heutagogy elements (i.e. self-learning, creativity, self-efficacy, flexible curriculum, learning resources, and flexible assessment). This is explaining that TVET educators have aware and make significant action to increase productivity and efficiency. This finding can be a benchmark for continuous process improvements that can help eliminate inefficiencies and ultimately improve education quality.